Research on Online Diagnosis of Electric Actuator based on Digital Signal Processor - Zhenguo Sun, Yonglei Yin, Sihong Wu (The International Journal of Multiphysics, 2024)
An electric actuator, which integrates power electronics technology, computer technology, sensor technology, and motor technology, is a new on-site terminal control device. Especially with the application of intelligent frequency conversion technology, the same device can have different operating speeds and breaking torques within a certain range. This feature is particularly suitable for different working conditions such as valve opening, closing, and operation. In this way, the product specifications and models are significantly reduced, which is conducive to production and user selection. At present, the prototype’s test has been completed, and all performance indicators have met the requirements of industry standards. Some technical indicators have even been improved compared with the same type of products of internationally renowned brands. Therefore,its small batch production is being prepared.